HUBUNGAN ANTARA PERTAMBAHAN BERAT BADAN IBU HAMIL DENGAN TAFSIRAN BERAT JANIN DI BPM NINIK ARTININGSIH, SST., M.Kes KELURAHAN BLOOTO KOTA MOJOKERTO - Ma?rifah, Asirotul; Ratna Fitri Ananda, Dita (JURNAL KEPERAWATAN SEHAT, 2015)
The diet and healthy lifestyle can help growing and fetal development in mothers womb, all intake consumed strive to fulfill the nutritional standards. The nutritional condition of pregnant women closely related with fetal wight will be born. The purpose of the result is to the know corelation of expectant mother’s wight gain with fetal weight interpretation in BPM Miss Ninik A in Blooto Village Mojokerto. The design of the study is analytic with cross sectional approach. The population is all the pregnant women in Trimester II and Trimester III as much as 25 people so be obtained 25 people for sample obtainable with purposive sampling. The independen variable in the study is expectant mother weight gain and the dependent variable is fetal weight interpretation. Data taken with the observation and weight scales and metlin. After the data was collected perform data processing and statistical tests continued by chi-square with the help of SPSS version 16.0. Calculation results showed significance (α) = 0,396. With the assumption if ρ < 0.05 Ho is Rejected so there is a corelation between maternal weight gain with fetal weight interpretation. The diet and good intake nutrient greatly affect weight gain and fetal weight interpretation normal in pregnancy, but not exactly intake nutrient and not exactly arrangement diet can affect to the weight gain in pregnancy and the fetal weight interpretation.Key word : Corelation, weight gain in pregnancy, fetal weight interpretation.